The secondary pore development model of coarse-grained deposition: A case study of the Xiazijie Formation in the Northwestern Margin of the Junggar Basin. Issue 3 (May 2023) - Ma, Yongping; Zhang, Xianwen; Wang, Guodong; Xu, Duonian; Guan, Xin; Pan, Shuxin; Qu, Yongqiang
The coarse-grained glutenite rock mass of the proximal fan delta is characterized by the blocky texture, mixing of gravels with varied sizes, high mud content, and low porosity and permeability, leading to difficulties in assessment and exploration of oil and gas enrichment regularities of tight glutenite. The Permian Xiazijie Formation in the northwest margin of Junggar Basin has a set of tight glutenite reservoirs, and the reservoir quality is an important controlling factor for oil and gas enrichment. Based on three-dimensional earthquake, casting thin sections, rock physical property, geochemistry, the sedimentary facies division, petrologic features, physical property regularities, pore types and diagenesis of Xiazijie Formation were analyzed. This research develops the pore evolution model of the coarse-grained deposition via the quantitative analysis of porosity evolution. First, during the rapid compaction, intensive mechanical compaction results in reduction of the original porosity from 29.8% to 15.1%. Secondly, the cement formed during the eodiagenesis destructs the reservoir space and leads to an average porosity loss of 6.5%. Third, dissolution effectively improves reservoir quality. It mainly dissolves the zeolite cement, and the porosity grows to 12.1% from 8.6%. The dissolution occurs during the main hydrocarbon expulsion stage of the source rock, which is in favor of hydrocarbon emplacement. Fourth, during the telodiagenesis with the deepening burial and intensifying pressure solution, siliceous and carbonate cement precipitate, the reservoir physical property is degraded again, the porosity loss is about 3.4%. After a series of complex diagenetic processes, the current tight glutenite reservoir comes into being, with the porosity of about 8.7%. The research results provide theoretical reference for coarse-grained glutenite reservoir prediction.